2017
DOI: 10.1038/s41598-017-13379-z
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Iran: Prospective Analysis from First Nationwide Diabetes Report of National Program for Prevention and Control of Diabetes (NPPCD-2016)

Abstract: We estimated proportions of different types of diabetes, comorbidities, treatment (the use of oral glucose-lowering agents and insulin), control (hyperglycemia, dyslipidemia and hypertension) and chronic microvascular and macrovascular complications among people with diabetes presenting to the tertiary-care academic diabetes outpatient clinics in Iran. This study is the prospective analysis of data (n = 30,202) from the registry of university-affiliated adult outpatient diabetes clinics in the country during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(218 citation statements)
references
References 44 publications
9
206
3
Order By: Relevance
“…Focusing on diabetes status, a national study on Iranian diabetic patients aged ≥18 years, reported the crude prevalence of CHD to be 25.1% for men and 23.2% for women [29]; which were comparable to our ndings (24.81% for men and 21.67% for women). Among diabetic populations of other countries, the age-standardized prevalence of CHD was found to be 4.43% and 4.76% among Chinese men and women with T2DM, respectively [30].…”
Section: Discussionsupporting
confidence: 88%
“…Focusing on diabetes status, a national study on Iranian diabetic patients aged ≥18 years, reported the crude prevalence of CHD to be 25.1% for men and 23.2% for women [29]; which were comparable to our ndings (24.81% for men and 21.67% for women). Among diabetic populations of other countries, the age-standardized prevalence of CHD was found to be 4.43% and 4.76% among Chinese men and women with T2DM, respectively [30].…”
Section: Discussionsupporting
confidence: 88%
“…2 In Iran, 11.4% of adults have been estimated to suffer from T2DM. 3 T2DM is related to several clinical complications including central obesity, hyperglycemia, dyslipidemia, oxidation of low-density lipoproteins (LDL), inflammation, hypertension, and the prothrombotic state. 4 Several studies have shown that obesity, especially abdominal obesity plays a major role in diabetes and metabolic complications associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…In a 7-year cohort study in Isfahan, the incidence of conventional risk factors of CVD in both sexes was as follows; hypertension, 22.5%; type 2 diabetes, 10.4%; overweight, 29.6%; and hypertriglyceridemia, 30.9% (75). Mediterranean countries including Italy (76) and France (77,78) have a reportedly lower prevalence of conventional CAD risk factors including diabetes and obesity than the Iranian population (79,80); but in a community-based survey in Greece, the prevalence of diabetes, hypertension, hypercholesterolemia and smoking were 11.1, 27.2, 23.8, and 38.9%, respectively; this may be due to reduced physical activity and lower consumption of the Mediterranean diet in recent decades (81). Furthermore, age is an independent risk factor for CAD (82).…”
Section: Frequency N (%) -------------------------------------------mentioning
confidence: 99%